PERGESERAN NARATIF DALAM KUMPULAN CERPEN PEREMPUAN BUTA TANPA IBU JARI KARYA INTAN PARAMADITHA: NARATOLOGI GÃ‰RARD GENETTE - Amir, Johar; Ridwan, Ridwan; Ramadhani, Fitri (SOSCIED, 2025)
This study aims to analyse the short story Perempuan Buta Tanpa Ibu Jari by Intan Paramaditha using GÃ©rard Genette's narratological approach, focusing on five main aspects: order, duration, frequency, mood, and narrative voice. Using a qualitative descriptive method with a combination of re-reading. The analysis shows that this short story uses analepsis (flashback) to build a non-linear narrative structure, creating a dramatic and immersive effect. Duration manipulation lengthens or summarises certain scenes to highlight emotional aspects and tensions in the story, while repetition of events reinforces narrative meaning and symbolism. Shifts in mood create an emotional contrast between introspective reflection and narrative tension, while the use of an autodiegetic narrator allows the reader to experience the story through the subjective perspective of the main character. Thus, the narrative techniques applied in this short story not only build a dynamic plot, but also enrich the thematic and emotional depth of the story